Optimal architecture of hybrid electric and thermal energy system - Zhao, Junming (Nanyang Technological University, 2022)
This dissertation aims to minimize the operating cost of the cogeneration microgrid embedded energy hub system, analyze the working status of each micropower source, and propose a system optimization scheduling strategy, so that the cogeneration microgrid embedded energy hub system can operate safely and stably while reducing the system operating cost. In this dissertation, the architecture of the cogeneration microgrid embedded energy hub system is first constructed, and the output power models of wind turbines, photovoltaic cells, lithium batteries and electric boilers are established respectively. Then, the short-term optimal scheduling objective function and constraints of the cogeneration microgrid embedded energy hub system are mathematically modelled, and finally the objective function is solved to obtain the system optimal scheduling result.